Inquiry-based instruction within a community of practice for gifted–ADHD college students. (January 2014) - Hua, Olivia (Liv); Shore, Bruce M; Makarova, Evgeniya
A number of characteristics are shared between attention-deficit hyperactivity disorder (ADHD) and gifted populations. They include issues with sustaining attention, following directions, and completing tasks. When an individual is both gifted and has ADHD (gifted–ADHD) he has unique educational needs that may put him at risk for underachievement. To date the literature largely addresses how to remediate perceived deficits. Less has been written about how to develop the talent of these twice-exceptional individuals. The present semi-autobiographical narrative proposes that inquiry-based instruction within an authentic community of practice can play an integral role in talent development for gifted–ADHD undergraduate students.